The University of Porto e-U project - Gil Coutinho (2005)
Students and staff from higher education institutions in Portugal expect nowadays to be able to access both the Internet and their campus intranets using wireless technologies. This nomadic broadband service is offered presently to the academic community across the country as a result of the Electronic University (e-U) national project.In this paper we first present a brief description of the University of Porto (UPorto) organization and of the e-U national project. We then focus on the IEEE 802.11 wireless LAN infrastructure, in particular in respect to its deployment at the UPorto campus. Key focuses are on the wireless mapping application (WiMa), developed locally at UPorto, and on the authentication architecture installed. User mobility at layer 2 (roaming) and the related AAA (authorization, authentication and accounting) functionalities are also discussed. The statistics of use show the growth in importance of wireless LAN technology over the last months at the UPorto campus. Present concerns and future developments are pointed out.